Assessing competency using simulation: the SimZones approach. (20th September 2019) - Roussin, Christopher; Sawyer, Taylor; Weinstock, Peter
Abstract : Introduction: Competency-based medical education (CBME) is a system of medical training that focuses on a structured approach to developing the clinical abilities of medical education graduates and practicing physicians. CBME requires a robust and multifaceted system of assessment in order to both measure and guide the progress of learners toward pre-established goals. Simulation has been proposed as one method for assessing competency in healthcare workers. However, a longitudinal framework for assessing competency using simulation has not been developed. Methods: Conjecture mapping methodology was used to map Miller's framework for competency assessment—'knows', 'knows how', 'shows how', and 'does'—to the five SimZones described by Roussin and Weinstock. The SimZones describe a system of organising the development and delivery of simulation-based education and offer a foundation for both guiding and organising assessment in a simulation context. Results: A conceptualised alignment of the SimZones with Miller's pyramid of assessment was developed, as well as a detailed conjecture map. SimZone 0 (auto-feedback) and SimZone 1 (foundational instruction) mapped to 'knows' and 'knows how'. SimZone 2 (acute care instruction) mapped to 'shows how'. SimZone 3 (team and system development) mapped to 'shows how'. SimZone 4 (real-life debriefing and development) mapped to 'does'. Conclusion: The SimZones system of competency assessment offers a robust, flexible, and multifaceted system to guide both formative and summative assessment in CBME. The SimZones approach adds to the many methods of competency assessment available to educators. Adding SimZones to the vocabulary of CBME may be helpful for the full deployment of CBME.